Urban digital economy, business model innovation and corporate ESG performance: A industry chain upstream and downstream perspective - Zhang, Shuhua (Edelweiss Applied Science and Technology, 2024)
Vigorously developing the digital economy is a future national strategy of the Chinese government, and the sustainable development of the industrial chain is a future challenge for Chinese enterprises. The environmental, social and governance (ESG) performance of enterprises is an important micro-indicator of sustainable development, which links the development of the digital economy with the safety of the industrial chain. In order to explore the mechanism and path of digital economy to enhance corporate ESG performance under the industry chain perspective, this paper conducts an empirical analysis with a sample of 4,482 listed companies in Shanghai and Shenzhen, China, from 2013 to 2022. The results of the study show that, first, the development of urban digital economy not only improves the ESG performance of enterprises in the jurisdiction but also enhances the overall ESG performance of the industry chain in which the enterprises are located. Second, the effect is significant in both the eastern and central and western samples, but there is heterogeneity in the nature of property rights, and the effect is more significant in the sample of state-owned enterprises. Third, although both green technological progress and business model innovation play a role in the influence mechanism in the transmission of the industrial chain, the influence of business model innovation is more significant in terms of size. This study complements the research on the relationship between digital economy and corporate ESG from the industry chain perspective.